Subnational capital markets in developing countries : from theory to practice - Freire, Mila.; Petersen, John E.; Huertas, Marcela; Valadez, Miguel; World Bank. (Washington, D.C. : World Bank ; New York, NY : Oxford University Press, 2004)
This book, prepared by staff members of the World Bank and selected guest contributors, consists of two parts. The first part comprises a framework to study subnational governments as borrowers and the array of credit markets in which they may operate. The second part consists of case studies that document the recent experience of 18 countries in developing markets for subnational borrowers and offer lessons about fostering responsible credit market access within a framework of fiscal and financial discipline. The book pools information on the issuing of municipal debt and its characteristics, analyses the role of macroeconomic conditions and market development in the success or failure of those borrowings, and suggests recommendations to guide ongoing efforts. The goal is to assist local governments in working as strategic partners in the development and strengthening of the capital markets in emerging economies.
Includes bibliographical references (p. 593-606) and index.
lje 13/07/16
Loans
Keywords: Capital market; Debts, Public; Subnational governments; Developing countries